Does Phosphodiesterase 11A (PDE11A) Hold Promise as a Future Therapeutic Target? - P. Kelly, Michy (Current Pharmaceutical Design, 2015)
Phosphodiesterase 11A (PDE11A) is the most recently discovered 3’, 5’-cyclic nucleotide phosphodiesterase. By breaking down both cAMP and cGMP, PDE11A is a critical regulator of intracellular signaling. To date, PDE11A has been implicated to play a role in tumorigenesis, brain function, and inflammation. Here, we consolidate and, where necessary, reconcile the PDE11A literature to evaluate this enzyme as a potential therapeutic target. We compare the results and methodologies of numerous studies that report conflicting tissue expression profiles for PDE11A. We conclude that PDE11A expression is relatively restricted in the body, with reliable expression reported in tissues such as the brain (particularly the hippocampus), the prostate, and the adrenal gland. Each of the four PDE11A splice variants (PDE11A1-4) appears to exhibit a distinct tissue expression profile and has a unique N-terminal regulatory region, suggesting that each isoform could be individually targeted with a small molecule or biologic. Progress has been made in identifying a tool PDE11A inhibitor as well as an activator; however, the functional effects of these pharmacological tools remain to be determined. Importantly, PDE11A knockout mice do exist and appear healthy into late age, suggesting a potential safety window for targeting this enzyme. Considering the implication of PDE11A in disease-relevant biology, the potential to selectively target specific PDE11A variants, and the possibility of either activating or inhibiting the enzyme, we believe PDE11A holds promise as a potential future therapeutic target.
Keywords: memory